Natural Scientific Language Processing and Research Knowledge Graphs: First International Workshop, NSLP 2024, Hersonissos, Crete, Greece, May 27, 2024, Proceedings - Rehm, Georg; Dietze, Stefan; Krüger, Frank (Lecture Notes in Computer Science; Lecture Notes in Artificial Intelligence, 2024)
This Open Access book constitutes the refereed proceedings of the First International Workshop on Natural Scientific Language Processing and Research Knowledge Graphs, NSLP 2024, held in Hersonissos, Crete, Greece, on May 27, 2024. The 10 full papers and 11 short papers included in this volume were carefully reviewed and selected from a total of 26 submissions. The proceedings aims to bring together researchers working on the processing, analysis, transformation and making use-of scientific language and research knowledge graphs including all relevant sub-topics.